2017
DOI: 10.1186/s12872-017-0546-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inaccuracies in arterial path length measurement on differences in MRI and tonometry measured pulse wave velocity

Abstract: BackgroundCarotid-femoral pulse wave velocity (cf-PWV) and aortic PWV measured using MRI (MRI-PWV) show good correlation, but with a significant and consistent bias across studies. The aim of the current study was to evaluate whether the differences between cf.-PWV and MRI-PWV can be accounted for by inaccuracies of currently used distance measurements.MethodsOne hundred fourteen study participants were recruited into one of 4 groups: Type 2 diabetes melltus (T2DM) with cardiovascular disease (CVD) (n = 23), T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 27 publications
(25 reference statements)
3
21
0
Order By: Relevance
“…This was not the case in the current study with the only variables significantly impacted by the new formula being BMI and waist circumference—both of which are known to affect the accurate path length measurement. 14 , 20 We found no significant shift in the magnitude of differences in PWV between those with and those without cardiovascular disease and no substantial change in the hazard ratios for PWV for prediction of future major adverse cardiovascular events and mortality.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…This was not the case in the current study with the only variables significantly impacted by the new formula being BMI and waist circumference—both of which are known to affect the accurate path length measurement. 14 , 20 We found no significant shift in the magnitude of differences in PWV between those with and those without cardiovascular disease and no substantial change in the hazard ratios for PWV for prediction of future major adverse cardiovascular events and mortality.…”
Section: Discussionmentioning
confidence: 57%
“…Multiple studies have documented significant differences between carotid–femoral PWV and central aortic PWV, 15 , 16 with this difference being markedly reduced when the true arterial path lengths are used in the carotid–femoral PWV calculation rather than the external distance measurements. 14 , 17 We are not the first to attempt to derive a formula for the calculation of the true arterial path length for use in PWV calculation. Weber et al 6 produced a calculation for distance being equal to the (height/4+7.28) from a population of 135 being investigated for coronary artery disease, but, however, used the distance from the ascending aorta to the aortic bifurcation as the comparator which is not representative of the path traveled by the pulse wave between the carotid and femoral artery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We can observe, from Figs 2 and 3 , that as PWV goes above 12 m / sec the error starts to increase. It is both because of the inherent measurement error 37 40 and also sparsity of data in that region. For smaller values of PWV , this behavior is less pronounced as data concentration is higher and also the measurement errors are smaller.…”
Section: Resultsmentioning
confidence: 99%
“…Even though c-f PWV is a valid measure of the arterial stiffness in the aortic and aorto-iliac vascular tree, it should be acknowledged that c-f PWV does not reflect the heterogeneity which occurs in various primary and secondary branches. A recent study by Weir-McCall et al demonstrated differences in carotid-femoral measured PWV and MRI measured aortic PWV, which can be for the most part be explained by use of simple surface measurements [ 55 ]. Nevertheless, distance estimation has been performed in a standardized way in this study.…”
Section: Discussionmentioning
confidence: 99%